Pro J2ME Polish Open Source Wireless Java Tools Suite - Virkus, Robert. (Apress : Imprint: Apress, 2005)
Pro J2ME Polish: Open Source Wireless Java Tools Suite is written for wireless and other mobile Java programmers who want to "polish" their efficiency and acquire in-depth knowledge about programming real-world J2ME applications. It also uncovers all common device limitations and quirks, and explains how these can be circumvented. The book describes the open-source tools collection J2ME Polish, and shows how the tools can be used for creating professional J2ME applications. Building multiple devices and multiple locales is easy after studying this book. Author Robert Virkus offers tips about the more hidden features of J2ME Polish, like the logging framework, the preprocessor, and the game-engine. You will learn to polish up your applications with the powerful GUI that enables you to design standard J2ME applications with simple CSS text files. You'll also learn to write portable, fast applications while using all available features on your target devices simultaneously.